Evaluation of Nutrient Composition and Bioactive Substances in Water Caltrop from Different Origins - Haizhen Si; Yang Yi; Limei Wang; Wenfu Hou; Hongxun Wang; Youwei Ai; Ting Min (Horticulturae)
This study analyzed eight origins of water caltrop: HH; XG; XT; ST; JY; CZ; YN; JX. The evaluations focused on visual appearance, nutritional quality, and bioactive substances. Additionally, the shells and pulp of the JY were examined for the same parameters. The results demonstrated that the JY exhibited the highest total phenolic content (121.74 mg GAE/100 g) and total flavonoid content (196.67 mg GAE/100 g). The XG demonstrated the highest water content (87.35%) and soluble protein content (15.36 mg/g). JX exhibits the highest total phenolic and flavonoid content, as well as the strongest DPPH radical scavenging rate in the fruit pulp, indicating its superior biological activity and antioxidant capacity compared to water caltrop from other regions. In addition, JX has the highest soluble solids and sugar content in fruit pulp, indicating a sweeter taste. The YN exhibited the highest pulp starch and lowest water content. Principal component analysis revealed that the pulp of the ST and the shell of the JY scored the highest. These findings provide valuable insights for evaluating and processing the nutritional quality of water caltrop from different sources and provide a theoretical basis for consumers to choose water caltrop according to their needs.